West Greenland salmon and climatic change. - Dunbar, M. J.; H. Thomson, Denis (Meddelelser om Grønland, 1979)
Climatic variations affecting the West Greenland marine region since the 16th century are reviewed in association with historical records of the Atlantic salmon(Salmo salar L.) in that area. There is evidence that the salmon, which are very abundant at present during their sea-life in West Greenland waters, were also present in some numbers in the years around 1600 and 1810. In all three periods the marine climate was cooling, following a warming phase. A possible hydrographic mechanism for this effect is suggested in the alternation of a strong zonal (west-east) climatic system over the North Atlantic region, giving warmer conditions in West Greenland, and periods of weakening of this zonal system and the appearance of anomaly easterly winds in South Greenland. The latter cause East Greenland Current water and Irminger Current water to increase in transport in the formation of the West Greenland Current, and are associated with a southward movement of the Iceland Low and a reduction in pressure gradient between the Iceland Low and the Azores High.